The Physical Health of Students of Hohhot No.36 Middle School, Inner Mongolia, China - Xiao, Jianwei (Pacific International Journal, 2023)
The physical health of Chinese high school students has always been a concern. According to statistics from the Chinese Ministry of Education, there are currently widespread problems among Chinese high school students, including a decline in physical fitness, an increase in obesity rates, and a high prevalence of myopia. To improve the physical health of Chinese high school students, the national and local governments have implemented a series of measures, such as promoting nationwide fitness activities, encouraging sports, improving dietary structures, and enhancing the quality of education. Meanwhile, many schools have also begun to pay attention to physical exercise, strengthening students’ physical education courses, providing various sports facilities and equipment, and encouraging students to actively participate in sports activities, to provide a better environment and conditions for the healthy development of high school students. This article investigates factors affecting the physical health of high school students and provides suggestions for improving their physical fitness by using literature, data, and testing methods. The study focuses on 120 students from Hohhot No. 36 High School and compares their physical fitness test results with those of other high school students across the country. By cultivating students’ physical fitness through various means, this study aims to improve students’ physical health and address their weaknesses in physical fitness.